DARI TANAH MENUJU KESADARAN ILAHIAH: REKONSTRUKSI KONSEP EVOLUSI SPIRITUAL DALAM FILSAFAT ISLAM KONTEMPORER - Mastori, Mastori; Hadi, Abdul; Faqihuddin, Ahmad; Milasmawati, Milasmawati; Hidayah, Muhammad Syarif (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
Abstract( In English). This article explores the integration of Islamic creation narratives with modern evolutionary theory through a philosophy of consciousness approach. By analyzing the thoughts of Muhammad Iqbal and Nidhal Guessoum in dialogue with transpersonal psychology (Kitson et al., Yaden) and the philosophy of consciousness (Chalmers), this study proposes the concept of the